Cytokine IL-12, Dengue in children: analysis of a unique relationship - Manoharan, Rakesh; Pasupathy, Umapathy; Ravichandran, Latha; Sivaprakasam, Elayaraja; V., Srinivasan; G., Krishna Sameera (International Journal of Contemporary Pediatrics, 2018)
Background: Dengue is a mosquito borne viral infection caused by one of the four serotypes of dengue viruses (DENV1-DENV4). The consequences of DENV infection range from asymptomatic condition, dengue fever (DF), or severe forms, such as dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). The host immune responses have been considered as the major factor responsible for dengue pathogenesis. In this study, the cytokine IL-12 is reviewed for its utility as potential biomarker of severe dengue disease. Methods: 120 children of paediatric age group with either dengue NS1 antigen or dengue IgM positive were included. Cases were classified as uncomplicated dengue (dengue without warning signs) and complicated dengue (dengue with warning signs and severe dengue). Clinical features and IL-12 (ELISA KIT) levels were analyzed in the study population. Results: Analysis of clinical features among the study groups revealed children with complicated dengue had persistent vomiting (95%), abdominal pain (80%), decreased urine output (50%), bleeding manifestations (83.3%), Hepatomegaly (70%) Haemoconcentration with concurrent thrombocytopenia (93.3%), altered coagulation profile (28.3%), ICU stay (54.7%), leukocytosis (15%), leucopoenia (66.6%) normal leucocytes, (18.4%). Analysis of IL-12 levels revealed children with complicated dengue showed significant elevation compared to controls and uncomplicated dengue. Conclusions: In our study IL-12 levels were significantly higher in complicated dengue patients in comparison with uncomplicated dengue patients as well as normal control population.